ManTool: Application as Manufacturing Tools for Resources Management based on GIS - Ika Arum Puspita; Arrivan Dika Santosa; Muhammad Agung Hambali; Faridhah Raehanisa Pribadi; Stevanus Yustiawan (School of Industrial and System Engineering, Telkom University, 2021)
Competition in the textile industry is very high. Companies must be able to meet market needs byproducing goods according to demand. In producing an item, it is necessary to design the amount ofraw material required. This study aims to publish geographic information system (GIS) basedapplication design as a tool in resource management. This application is named ManTool. ManToolcan provide a reminder when raw material stocks run out. With this system, the company can orderraw materials, and the production system continues to run well. This system is designed based on aGeographical Information System (GIS), it is easier for companies to determine which supplier ofraw materials to choose. The method of making this system is by using the waterfall method. Thismethod produces the right system because each stage is identified sequentially. The result of thisresearch is a geographic information system-based application. With this application, the companywill get a notification when the raw material runs out, and the company will get the right supplier'srecommendation to buy raw material.